An Omni‐Healable Supercapacitor Integrated in Dynamically Cross‐Linked Polymer Networks. (21st April 2017) - Wang, Zhikui; Pan, Qinmin
Abstract : Self‐healing will greatly improve the reliability of an energy‐storage device in case of physical damage, but the challenge remains in assembling such a smart device capable of repairing all its electroactive components simultaneously. Here, an omni‐healable supercapacitor that can spontaneously repair its electrolyte, electrodes, and even the interfaces between them in ambient conditions after mechanical damage is reported. The goal is achieved by integrating electrolyte and electrode materials into a dynamic poly(vinyl alcohol)‐based network cross‐linked by diol‐borate ester bonding. The capacitor fast restores its configuration, mechanical properties, and capacitive performances during all 15 breaking/healing cycles without external stimulus, regardless of the breaking positions. Interestingly, the capacitor can tolerate various physical deformations and even tailoring without performance deterioration. The investigation offers a facile and versatile strategy to construct an intrinsically self‐healable energy‐storage device that has potential application for portable/wearable electronics, smart apparels or flexible robots, and so on. Abstract : An omni‐healable supercapacitor, which autonomously repairs its electrolyte, electrodes, and the interfaces between them after mechanical damage, is fabricated by integrating the electroactive components in polymeric networks cross‐linked by dynamic diol‐borate ester bonding. The omni‐healability occurs at least 15 times under ambient conditions without stimulus. The capacitor can tolerate various physical deformations and even tailoring without performance deterioration.